Autonomous guidance and conflict avoidance for multiple Unmanned Aerial Vehicles (UAVs) in urban environments - Hughes, Merrick (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.